Collective Magnetism in 2D Polymer Made of C‐Doped Triangular Boron Nitride Nanoflakes. Issue 5 (26th March 2021) - Anindya, Khalid N.; Rochefort, Alain
Abstract: The electronic and magnetic properties of 2D polymer built from triangular boron nitride monomers (tBN) doped with C atom are investigated with first‐principles DFT calculations. Polymers made of pure tBN are insulators as pristine h‐BN, but substituting the central B(N) by C atom in tBN(NB) spontaneously leads to the creation of a spin‐polarized ground state polymer. Moreover, the ground state of C‐doped polymer is an open‐shell semiconductor in which both Dirac and flat bands coexist nearby Fermi level while the nearest excited state is a closed‐shell semi‐metal where the Dirac cone crossed Fermi level. The triangular shape of the monomer, the nature of atomic substitution, and the relative position of C‐dopant among the 2D polymer are contributing to create a strong collective magnetism in conjunction with a significant orbital overlap between C‐dopants separated by 1.0 nm. This collective magnetism is totally suppressed in (CtBN‐CtNB) copolymer arrangement, where the material shows a semiconducting gap with no spin‐polarization and strongly localized states around Fermi level. The results predict a 2D material with long range metal free magnetic ordering, in conjunction with high carrier mobilities from Dirac bands and anisotropic shapes of topological states, that opens the door for 2D organic spintronic applications. Abstract : From DFT calculations, a new family of non‐conjugated 2D Kagome polymer is predicted where strong long‐range spin and orbital coupling coexist, along with topological edge states around the Fermi level. The C‐dopant in triangular‐BN monomers acts as a superatom that enables the long‐range coupling. In addition, the co‐polymer virtually showed non‐dispersive states around Fermi level, suggesting a Mott‐insulating phase.